How to succeed as an independent consultant - Holtz, Herman (John Wiley & Sons, Inc., 2004)
No matter what your field of expertise, this book will help you win clients through a variety of practical, proven techniques you'll find only here. Packed with real-world, effective business-driving tactics-as well as up-to-the-minute advice on getting the most out of new technologies-this helpful guide will show you how to market yourself in new ways, soar over IRS hurdles, and grow your home-office operation into a thriving practice.